2004
DOI: 10.1086/421503
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofPlasmodium falciparumby Photodynamic Excitation of Heme‐Cycle Intermediates Derived from δ‐Aminolevulinic Acid

Abstract: Transfusion-transmitted malaria (TTM), especially that caused by Plasmodium falciparum, is of great concern in malaria-endemic areas. As a result of increased international travel, migration, and the spread of drugresistant parasites, TTM is also a growing problem in industrialized nations. An effective and inexpensive means of inactivating malaria parasites in blood products would represent an important advance. In this report, we demonstrate that photoactivation of plasmodial heme-cycle intermediates, derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 66 publications
1
20
0
4
Order By: Relevance
“…) . It would seem that each of these biosynthetic pathways has the potential for exploitation by ALA‐based PDT and consistent with this observation, a recent in vitro study demonstrated that the technique was able to induce the accumulation of endogenous porphyrins in P. falciparum when present in parasitized erythrocytes with inactivation of the organism resulting . It was suggested by these latter authors that ALA‐based PDT should be further tested for the potential to act as a blood decontaminant not only for malaria parasites but also for other parasitic threats such Babesia spp, Toxoplasma gondii, Trypanosoma cruzi, and Leishmania spp.…”
Section: The Inactivation Of Parasites Yeasts and Fungi By Ala‐basedmentioning
confidence: 57%
“…) . It would seem that each of these biosynthetic pathways has the potential for exploitation by ALA‐based PDT and consistent with this observation, a recent in vitro study demonstrated that the technique was able to induce the accumulation of endogenous porphyrins in P. falciparum when present in parasitized erythrocytes with inactivation of the organism resulting . It was suggested by these latter authors that ALA‐based PDT should be further tested for the potential to act as a blood decontaminant not only for malaria parasites but also for other parasitic threats such Babesia spp, Toxoplasma gondii, Trypanosoma cruzi, and Leishmania spp.…”
Section: The Inactivation Of Parasites Yeasts and Fungi By Ala‐basedmentioning
confidence: 57%
“…Akuatik ekosistemde parazit kontrolünü sağlamak için klorofil türevleri kullanılmış ve bu bileşiğin sinek larvaları üzerine öldü-rücü etki gösterdiği saptanmıştır (16) . Bundan başka kan ürünlerinden Malaria etkeninin inaktive edilmesinde de FDAT yararlanıla-bileceği belirtilmektedir (44) .…”
Section: Fotoantimikrobiyallerin Mikroorganizmalara Etkisiunclassified
“…Phthalocyanines (one of the most effective, HOSiPcOSi(CH,),(CH,),N(CH,), (Pc 4) ), illuminated by red light, manifested the photoinactivation of P. falciparum parasitized in red cells in a dose-dependent manner and could be used to make blood components safe [151]. Another study demonstrated that ALA-induced inactivation of plasmodial heme-cycle intermediates, by exposure to white light, reduced P. falciparum in culture to levels such that they were not detectable by light microscopy nor by lactate dehydrogenase assay [152]. …”
Section: Photodynamic Therapy As An Anti-infectivementioning
confidence: 99%